2021
DOI: 10.1007/s11104-021-04984-z
|View full text |Cite
|
Sign up to set email alerts
|

Applying foliar magnesium enhances wheat growth in acidic soil by stimulating exudation of malate and citrate

Abstract: Aims Aluminium toxicity in acidic soils adversely affects wheat growth. Foliar-applied magnesium (Mg) contributes to mitigating soil acidity stress in wheat, but the mechanisms are unknown. This study explored the mechanism of foliar-Mg mediated enhancement of wheat growth in acidic soil. Methods Two contrasting near-isogenic wheat (Triticum aestivum L.) genotypes differing in Al resistance (Al-sensitive ES8 and Al-resistant ET8) were grown to the vegetative stage (Zadoks 24) in a reconstituted acidic soil (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Moreover, these inorganic ions were crucial for Al’s detoxification process. According to the study, Mg 2+ and K + can help release organic acid anions and maintain electrolyte balance ( Kibria, Barton & Rengel, 2021 ). By increasing Mg uptake, the overexpression of the Mg transporter gene AtMGT1 reduced Al toxicity ( Deng et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these inorganic ions were crucial for Al’s detoxification process. According to the study, Mg 2+ and K + can help release organic acid anions and maintain electrolyte balance ( Kibria, Barton & Rengel, 2021 ). By increasing Mg uptake, the overexpression of the Mg transporter gene AtMGT1 reduced Al toxicity ( Deng et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Foliar sprays are often applied to crop species in many areas of the world [ 20 , 21 , 22 , 23 , 24 ], but the response of plants to the treatments is often variable as described for other elements [ 17 , 19 ]. Hence, specific trials are required for attempting to clarify which are the major factors influencing the absorption of foliar agrochemical treatments as a prerequisite for optimizing the efficacy of foliar sprays in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite leaf wettability being an important preliminary variable affecting foliar absorption, transport across the leaf epidermis may also be limited by the physico-chemical nature of the cuticle and cell wall [ 18 ]. Various studies carried out with different crop species reported positive plant responses and increased tissue Mg values in association with the application of foliar Mg sprays, e.g., [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that citric acid-modified biochar can reduce the bioavailability of Cd in soil [ 10 ]. Citric acid could regulate the balance of anions and cations in rice by mediating the balance of cations and anions within plants and subsequently affecting the transport of mineral elements within plant tissues [ 11 , 12 ]. Exposed to 50 μM Cr stress, the CA content significantly increased in rice.…”
Section: Introductionmentioning
confidence: 99%